The Specialty of mycology and Transcendence in Ecuador and the world - Lazo Salazar, Ramón (Revista Universidad de Guayaquil, 2012)
In approaching this issue on the Significance of Mycology and Parasitology I must emphasize that I was not wrong in choosing them, the academic and scientific production is proof of this election, since I have been contributing to the medical community with no conditions existing in our country, showing their best knowledge in both specialties. Starting the selection of these specialties, I applied to Dr. Alfredo Ceballos Carrión, Professor of Pediatrics, a topic for the Thesis, who suggested the name of Histoplasmosis (1)